2021
DOI: 10.1038/s41419-021-03416-1
|View full text |Cite
|
Sign up to set email alerts
|

Sequential targeting of YAP1 and p21 enhances the elimination of senescent cells induced by the BET inhibitor JQ1

Abstract: Chondrosarcoma (CHS) is the second most common bone malignancy with limited therapeutic approaches. Our previous study has found that Yes associated protein 1 (YAP1) is downregulated in CHS cells treated with bromodomain and extraterminal domain (BET) inhibitor JQ1. However, the precise role of YAP1 in CHS is largely unknown. Herein, we found that YAP1 expression was upregulated in CHS tissues, and positively correlated with its grading score. Loss of YAP1 inhibited CHS proliferation and induced cellular senes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Furthermore, the knockdown of YAP1 led to increased expression of the cell cycle inhibitor p21 Cip1/Waf1 ( Figure 2 A). These findings are in accordance with recently reported findings that pharmacological inhibition of YAP1 or YAP1 depletion led to increased expression of p21 and the induction of senescence [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the knockdown of YAP1 led to increased expression of the cell cycle inhibitor p21 Cip1/Waf1 ( Figure 2 A). These findings are in accordance with recently reported findings that pharmacological inhibition of YAP1 or YAP1 depletion led to increased expression of p21 and the induction of senescence [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, as recently reported for rhabdomyosarcoma [ 46 ], it is possible that dasatinib might not be sufficient to phenocopy the effects of RASSF1A, and that the combination of dasatinib with RASSF1A-activating drugs such as DNMTi is needed to suppress YAP1 activity and YAP1-mediated FOXM1 and ERα expression. Notably, it was reported that sequential targeting of YAP1 and p21 led to the elimination of senescent tumor cells [ 39 ]. As senescent cells may contribute to disease recurrence after cancer therapy, the potential clinical application of YAP1 inhibition together with RASSF1A-activating drugs may also require sequential targeting of p21 to shift senescent cells into apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…P16 and P53‐P21 are two canonical pathways that control senescence. [ 40,41 ] Our data showed that knockdown of P16 and P21 eliminated Notch‐induced senescence. These findings collectively confirmed the role of the Notch‐Sirt1‐P53‐P21 or Notch‐Sirt1‐P16 axis in regulating LSEC senescence (Figure 7K).…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, H&E (three native and three decellularized) and DAPI (three native and three decellularized) images were analyzed quantitatively by counting cell nuclei using ImageJ ITCN plug-in. 44,45 IHC images [collagen IV (three images) and laminin (three images)] were analyzed quantitatively by measuring the percentage of stained area using ImageJ software. 46…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%